Relationship between iHOT12 and HOS scores in hip pain patients. Issue 1 (12th February 2020) - Brand, Jeff; Hardy, Rich; Tori, Aerika; Fuchs, Hannah; Sungur, Engin; Monroe, Emily
Abstract: To determine if scores of the International Hip Outcome Tool-12 (iHOT12) and the Hip Outcome Score (HOS) correlate with one another in hip pain patients. Patients reporting to an orthopedic clinic for their scheduled appointment for hip pain were given a paper survey consisting of the iHOT12 and the HOS. Demographic information [age, weight, height and body mass index (BMI)] was obtained by chart review. Overall, 114 patients were invited to voluntarily complete the surveys of which 23 declined. Our sample consisted of 91 (57 female and 34 male) patients (80% response rate). The HOS (iHOT12) explained 62% of the variation in iHOT12 (HOS) by using a linear model (Pearson's correlation( r ) is 0.79, P < 0.001). Age, weight, BMI, gender and arthritis did not show a statistically significant predictive power explaining HOS. However, only gender had a 'statistically' significant predictive power explaining iHOT12 ( P = 0.007). The relationship between the two scores are stronger for males ( r = 0.81, P < 0.001) compared with females ( r = 0.77, P < 0.001). The proportion of variations explained on one of the scores by the other are 0.66 for males and 0.59 for females. HOS score together with gender explained 64% of the variation in iHOT12 by using a linear model. iHOT12 together with the non-statistically significant gender term explained 62% of the variation in HOS by using a linear model. It may not be necessary to collect both the iHOT12 and HOS, since the predictive power of one on the other is high. Collecting HOS together with information on gender is preferable compared with collecting iHOT12. Level of evidence : Level III.